Cross-cultural Comparison of Perceptions and Knowledge About Electroconvulsive Therapy Among Adults Who Screened Positive for Depression in the United States, India, and China. Issue 4 (December 2021) - Tsai, Jack; Huang, Minda; He, Hongbo; Selek, Salih; Rosenheck, Robert A.
Abstract : Objective: Despite the established efficacy of electroconvulsive therapy (ECT), negative perceptions and inaccurate knowledge about ECT in the United States and other countries persist. This study examined ECT perceptions and knowledge in the 3 most populous countries in the world. Methods: We recruited participants who screened positive for depression on the Patient Health Questionnaire 9 (PHQ-9) in the United States (n = 1643), India (n = 1469), and China (n = 328) and compared responses on the ECT–Perception and Knowledge Scale. Results: Although the US sample had significantly higher PHQ-9 scores than the India and China samples, the US sample was less likely to have been offered ECT or to have ever received ECT. Moreover, the US sample scored lower on the ECT Perception and Knowledge subscales than the other samples indicating more negative perceptions and inaccurate knowledge about ECT. Across samples, there were moderate fears about ECT being painful or causing brain damage, and misconceptions about ECT being outdated and adverse effects of induced seizures. Higher PHQ-9 scores were correlated with more negative perceptions. Conclusions: Greater public education is needed about ECT, particularly in the United States. Misperceptions and lack of knowledge may hinder utilization of ECT in India, China, and the United States.